КОРХОНА ЗАХИРА (РЕЗЕРВ) КАПИТАЛИНИНГ БУХГАЛТЕРИЯ ҲИСОБИНИ ТАКОМИЛЛАШТИРИШ (Scientific journal of the Fergana State University, 2023)
The article found a definition of the solution of the problem, available for accounting and writing off reserve capital as part of the equity of economic entities.